2010
DOI: 10.1089/ten.tea.2009.0720
|View full text |Cite
|
Sign up to set email alerts
|

Ligament-Derived Matrix Stimulates a Ligamentous Phenotype in Human Adipose-Derived Stem Cells

Abstract: Human adipose stem cells (hASCs) can differentiate into a variety of phenotypes. Native extracellular matrix (e.g., demineralized bone matrix or small intestinal submucosa) can influence the growth and differentiation of stem cells. The hypothesis of this study was that a novel ligament-derived matrix (LDM) would enhance expression of a ligamentous phenotype in hASCs compared to collagen gel alone. LDM prepared using phosphate-buffered saline or 0.1% peracetic acid was mixed with collagen gel (COL) and was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 112 publications
(120 reference statements)
4
48
0
Order By: Relevance
“…Our findings indicate that the regulatory effects of tECM on tendon cell behavior also apply to ASCs. Consistent with our results, Little et al 42 found increased proliferation and partial adoption of tendon phenotype by ASCs seeded on acellular tendon/ligament matrix. The tECM contains not only collagen but also a number of Most fibers in the aligned scaffold were oriented at between 80°and 100°with respect to cross axis.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings indicate that the regulatory effects of tECM on tendon cell behavior also apply to ASCs. Consistent with our results, Little et al 42 found increased proliferation and partial adoption of tendon phenotype by ASCs seeded on acellular tendon/ligament matrix. The tECM contains not only collagen but also a number of Most fibers in the aligned scaffold were oriented at between 80°and 100°with respect to cross axis.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings and those of others have shown that ASCs exhibit multipotent differentiation capabilities in the mesenchymal lineage, similar to other adult stem cells such as MSCs, with evidence of adipogenic, chondrogenic, myogenic, neurogenic, osteogenic, and tenogenic differentiation [36,53,86]. Similarly, the culture conditions used to induce lineage-specific differentiation of ASCs generally are similar to those used for MSCs; although increasing evidence indicates that different adult stem cells possess unique characteristics and properties depending on their site of origin.…”
Section: Discussionsupporting
confidence: 84%
“…48 ECM proteins are generally well conserved among different species and, as such, may provide the opportunity for use as functional scaffolds for cell attachment, proliferation, and differentiation. 26,27,29,36,49 We previously showed that CDM, a porous scaffold derived from articular cartilage, is capable of inducing chondrogenic differentiation of ASCs without exogenous growth factors. 28 By crosslinking the CDM in a genipin solution (0.5%, 0.05% and 0.005%) at 37°C for 3 days, constructs were produced that were microscopically unique relative to noncrosslinked CDM, though similar to the unmodified matrix, genipin-crosslinked materials were highly porous (94.7%-95.9%).…”
Section: Discussionmentioning
confidence: 99%